Reversible posterior leukoencephalopathy syndrome in post streptococcal glomerulonephritis - Yubbu, Putri; Abd Hamid, Mohd Zaini; Jamaluddin, Johan Aref; Kee, Sze Ying; Mohd Fakharuddin, Mohd Feizel Alsiddiq; Othman, Norlijah; Ting, Tzer Hwu (2012)
Reversible Posterior Leukoencephalopathy syndrome (RPLS) is a uncommon neurological disorder among pediatric population. Clinical features started with decreased alertness and activity, and associated with headache, visual changes, altered mental status such as seizures, confusion and abnormal behavior. Radio imaging findings commonly present typical changes in the white matter located in the posterior regions of the cerebral hemisphere and cerebellum. This syndrome commonly associated with hypertension, ecclampsia, renal failure or the used of some immunosuppression medications especially cyclosporine and tacrolimus. We describe a previously healthy 9-year-old boy who presented with acute post-streptococcal glomerulonephritis, and he developed neurological symptoms of posterior leukoencephalopathy syndrome with hypertensive crisis. His CT scan shows typical changes of non enhancing white matter with hypodensities at the occipital and parietal temporal areas. He had a rapid resolution of neurological symptoms with adequate treatment of hypertension. He was discharged well after 14 days in the ward.